基于COSMOS/Works的数控机床主轴箱模态分析及优化设计 - 邱海飞; 王增强 (Jixie chuandong)
The finite element model of NC Machine spindle box is set up by COSMOS/Works,and modal analysis of the spindle box is done,then the natural frequencies and the vibration modes are calculated.On that basis,the dynamic characteristic of spindle box is optimized through defining multi structure sizes as design variable.Fundamental frequency of the spindle box is increased obviously after optimizing;as a result,damping property of it is enhanced effectively.A group of structural parameters with fine dynamic characteristic are calculated,which offer significant referents to structure design of spindle box.